1987
DOI: 10.1038/330168a0
|View full text |Cite
|
Sign up to set email alerts
|

Non-responsiveness to a foot-and-mouth disease virus peptide overcome by addition of foreign helper T-cell determinants

Abstract: Study of the immune response to synthetic antigens has shown that uncoupled peptides can realize their potential as vaccines only if they contain domains that react with helper T-cell receptors and Ia antigens in addition to antibody binding sites. Here we consider whether genetically restricted non-responsiveness to an uncoupled peptide could be overcome by synthesizing a peptide with an additional helper T-cell epitope from a different protein. We demonstrate that H-2d mice, which are non-responders to the 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
78
0

Year Published

1988
1988
2003
2003

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 201 publications
(82 citation statements)
references
References 0 publications
4
78
0
Order By: Relevance
“…Many approaches towards subunit vaccines for FMDV have been made (e.g. Kleid et al, 1981 ;Bittle et al, 1982;Winther et al, 1986;Clarke et al, 1987;Francis et al, 1987) and, although significant progress has been made, the most immunogenic particle apart from the virus itself is the 'empty' viral capsid (Rowlands et al, 1975). A major problem associated with FMDV vaccines has been outbreaks occurring as a result of improperly inactivated vaccines.…”
Section: Studies On the Cleavage Specificity Of Fmd V 3c Proteasementioning
confidence: 99%
“…Many approaches towards subunit vaccines for FMDV have been made (e.g. Kleid et al, 1981 ;Bittle et al, 1982;Winther et al, 1986;Clarke et al, 1987;Francis et al, 1987) and, although significant progress has been made, the most immunogenic particle apart from the virus itself is the 'empty' viral capsid (Rowlands et al, 1975). A major problem associated with FMDV vaccines has been outbreaks occurring as a result of improperly inactivated vaccines.…”
Section: Studies On the Cleavage Specificity Of Fmd V 3c Proteasementioning
confidence: 99%
“…The intraperitoneal inoculation of FMDV produces death in suckling mice, and this has been extensively exploited to titrate virus infectivity. Likewise, FMDV can be adapted, by serial passages, to produce clinical symptoms in guinea-pigs, an animal model that has been used mostly for immunological analyses [98].…”
Section: The Virus and The Diseasementioning
confidence: 99%
“…However, the immunogenicity of these peptide constructs in a number of host species was substantially lower than that of conventional vaccines (reviewed in [55,79]). In the following years, the concept that immunogenic peptides should also include viral T cell epitopes to provide an adequate co-operation with immune B lymphocytes to induce an effective neutralising antibody response, became generally accepted [39,55,58,79,98,194,227]. Such T cell peptides should ideally be recognised by T lymphocytes in the context of alleles of MHC class II frequently represented in the populations of the natural hosts [194].…”
Section: Peptide Vaccinesmentioning
confidence: 99%
“…T. Collen and T. R. Doel Conjugation of B and T cell epitopes (Cox et al, 1988) and collinear synthesis of the same (Borras-Cuesta et al, 1987 have been shown to influence the immunogenicity of peptide antigens. Furthermore, the addition of T cell epitopes to peptides with known B cell activity (Good et al, 1987;Francis et al, 1987b) has been shown to overcome major histocompatibility complex restriction, a known problem with peptide vaccines. Thus, for the development of an effective synthetic FMD vaccine there is a clear need to demonstrate T cell epitopes within the proteins of FMDV that are recognized by a natural host.…”
Section: Introductionmentioning
confidence: 99%